2013
DOI: 10.1021/jp4095485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Unimolecular Decomposition Pathways for Carboxylic Acids of Relevance to Biofuels

Abstract: Quantum mechanical molecular modeling is used [M06-2X/6-311++G(2df,p)] to compare activation energies and rate constants for unimolecular decomposition pathways of saturated and unsaturated carboxylic acids that are important in the production of biofuels and that are models for plant and algae-derived intermediates. Dehydration and decarboxylation reactions are considered. The barrier heights to decarboxylation and dehydration are similar in magnitude for saturated acids (∼71 kcal mol(-1)), with an approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 69 publications
3
37
0
Order By: Relevance
“…19 Ketene 3 19,20 has been reported experimentally, 21 while 4 may have been detected, 19 and substituted derivatives of 4 are known. 22 The formation of 4 by the dehydration of 3-butynoic acid has also been studied computationally, 23 as has the structure of isomer 5.…”
Section: Structure Bonding and Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…19 Ketene 3 19,20 has been reported experimentally, 21 while 4 may have been detected, 19 and substituted derivatives of 4 are known. 22 The formation of 4 by the dehydration of 3-butynoic acid has also been studied computationally, 23 as has the structure of isomer 5.…”
Section: Structure Bonding and Spectroscopymentioning
confidence: 99%
“…Computations have been used to study the dehydration of unsaturated acids such as 70 forming the extended ketene 71, 67 as well as of other unsaturated acids to the corresponding ketenes. 67 In a separate investigation dehydration of the dienyl acid 72 to the vinyl extended ketene 73 was included (Scheme 36).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most promising methods for the conversion of biomass to hydrocarbons is through deoxygenation of fatty acids [7,9,10] . In the absence of a metal catalyst, pyrolysis of fatty acids proceeds via competing decarboxylation and dehydration pathways [11] . Pioneering work by Sabatier has shown that deoxygenation of carboxylic acids proceeds via either decarboxylation, dehydration with decarbonylation, or a combination of both, [12] illustrated by Eqs.…”
Section: Introductionmentioning
confidence: 99%
“…In a more comprehensive study of the unimolecular reaction pathways for carboxylic acids of relevance to biofuels Clark et al 45 found that α,β-unsaturated acids, of which 2,4-pentadienoic acid is a member, were more prone to decarboxylation than dehydration in comparison to the analogous saturated acids. Their results for senecioic acid, (CH 3 ) 2 CCH−COOH, very closely match ours for 2,4-pentadienoic acid.…”
Section: -Methyl-2(3h)-furanone Skorianetz and Ohloffmentioning
confidence: 99%